Characterization of Ti-6Al-(4V-7Nb-4Mo) Biomedical Alloys Produced by Powder Metallurgy Method - AYGÜL, EBUZER; YALÇINKAYA, SENAİ (SPRINGER, 2020)
Pure titanium and titanium-based alloys are the most widely used metallic biomaterials in biomedical applications. At that, the Ti-6Al-4V alloy is considered as the most commonly exploited alloy among all alloys that contain titanium. However, it is known that the vanadium metal that constitute this alloy has a potential toxic effect. In this study, the powder metallurgy (PM) method was used for the production of pure-Ti, as well as Ti-6Al-4V, Ti-6Al-7Nb, and Ti-6Al-4Mo alloys. Niobium and molybdenum elements, one of the alloying metals, have been proposed as a substitution of vanadium due to its possible toxic effects. Produced samples were characterized by SEM, EDX, XRD, as well as microhardness, density, and Tafel extrapolation method. The analysis results showed that microstructure of pure titanium and titanium-based alloys differ. Besides, the XRD analysis showed that the phases of doped metals (Nb, V, and Mo) were found as Al0.23Nb0.07Ti0.70, Ti0.80V0.20, and AlMoTi3. Microhardness and Tafel extrapolation values were quite remarkable by comparing them to each other. The main important result of the research was obtained pure titanium and titanium alloys with homogeneous microstructure produced by the powder metallurgy method.
Keywords: pure titanium; Ti-alloys; powder metallurgy method; characterization; TITANIUM